Entre estigmas e distinções: a estruturação das posições sociais de sem-terra e assentados na região estancieira do Rio Grande do Sul - Zanella, Francis Casagranda (2017)
The present work analyzes how happens the process of insertion of beneficiary populations of the rural settlements policy in the structure of social positions of the municipality of Santa Margarida do Sul in the state of Rio Grande do Sul (Brazil). This municipality is located in a space that, since the end of the eighteenth century, is characterized by the occupation and hegemony by landlords called ranchers. This research is based on interviews with beneficiaries of the policy of rural settlements and with the former residents of the municipality, besides direct observation in situations of coexistence with each one of these groups. It is observed that settler populations began to systematically occupy positions in the region only in the mid-80s, and in the municipality this occurred in the year 2008. Starting from a migrant condition, marked by clashes in the field of agrarian conflicts, it is visualized how the settlers acquire an outsider position in relation with the former residents, the here called citizens. It establishes a set of relations determined by the asymmetries of power and cohesion between the group identified as former residents and the group of new entrants settlers. In a complexing way of the understanding of social conditions and positions, it is proposed here to construct an analysis of the duality settlers/citizens within two temporalities. Firstly, a static perspective analysis, in which the arrival of the landless in front of the citizens generated a perception of groups with relative internal homogeneity, characterizing an initial moment of the process of rural settlement in which the positions are tight. In this sense, objectivefild the meanings constructed in the tense moments of disputes in the field of agrarian conflicts are objectified, moments that characterized a period where the condition of citizens and landless is of groups in opposition. In a second moment, in addition to an analysis of static positions between groups, we try to understand what are the agents and objectives at play when approximations are made. Networks of economic and political relationships are visualized, which are built from the entry of settlers into different networks of sociability, such as the Municipal Public Power. As the settlers show different competences, and these become recognized and legitimized or delegitimized, a new condition opens up where settlers and citizens are constituted as groups in differentiation. In other words, after an initial period of installation of the rural settlement, the relationship between settlers and citizens can be understood by complex networks of relations, where generalizing notions such as 'aversion' or 'integration' do not account for the diversity of situations.